X-shooting GRBs at high redshift: probing dust production history. Issue 1 (19th July 2018) - Zafar, T; Møller, P; Watson, D; Lattanzio, J; Hopkins, A M; Karakas, A; Fynbo, J P U; Tanvir, N R; Selsing, J; Jakobsson, P; Heintz, K E; Kann, D A; et al.
ABSTRACT: Evolved asymptotic giant branch (AGB) stars and Type Ia supernovae (SNe) are important contributors to the elements that form dust in the interstellar medium of galaxies, in particular, carbon and iron. However, they require at least a Gyr to start producing these elements, therefore, a change in dust quantity or properties may appear at high redshifts. In this work, we use extinction of γ-ray burst (GRB) afterglows as a tool to look for variations in dust properties at z ≥ 3. We use a spectroscopically selected sample of GRB afterglows observed with the VLT/X-shooter instrument to determine extinction curves out to high redshifts. We present 10 new z ≥ 3 X-shooter GRBs of which six are dusty. Combining these with individual extinction curves of three previously known z ≥ 3 GRBs, we find an average extinction curve consistent with the SMC-Bar. A comparison with spectroscopically selected GRBs at all redshifts indicates a drop in visual extinction ( A V ) at z > 3.5 with no moderate or high-extinction bursts. We check for observational bias using template spectra and find that GRBs up to z ∼ 8 are detectable with X-shooter up to A V ∼ 0.3 mag. Although other biases are noted, a uniformly low dust content above z > 3.5 indicates a real drop, suggesting a transition in dust properties and/or available dust building blocks. The remarkable increase in dust content at z < 3.5 could arise due to carbon and possibly iron production by the first carbon-rich AGB and Type Ia SNe, respectively. Alternatively, z > 3.5 dust drop could be the result of low stellar masses of GRB host galaxies.